KNOWLEDGE, ATTITUDE, AND PRACTICE ON DIABETIC FUNDUS EXAMINATION AMONG GENERAL PRACTITIONERS IN PUSKESMAS OF BANDUNG CITY - Nina Ratnaningsih; mayang rini; Syumarti Syumarti; iwan sovani; degiana syabdini; medissa medissa (Indonesian Vitreoretinal Society, 2021)
Introduction: The prevalence of Diabetic Retinopathy (DR) and Vision Threatening Diabetic Retinopathy (VTDR) in Greater Bandung on 2017 was 24,7% and 9% respectively. It mean almost 30% DR fall into VTDR, although it could be prevented. Fundus examination in primary level of prevention is important to prevent VTDR, and potential barriers on it included knowledge, attitude, practice and related factors should be overcome. The objective of this research was to assess knowledge, attitude, practice (KAP) and related factors on diabetic fundus examination among GPs in Puskesmas of Bandung City. Method: This was a population based cross sectional study conducted on April-June 2020, involving 115 GPs at 62 Puskesmas of Bandung City who fulfilled the eligibility criteria by purposive sampling. It used self administered KAP questionnaire on diabetic fundus examination. The data were presented in descriptive and analytical explanation using Chi-square with p value of 0,05 as statistical significant result . Result: The mean of knowledge and attitude on fundus examination were 70,67 (95% CI ± 3,26), 72,87 (95% CI ± 2,61) respectly, included in good criteria, but Practice was poor for 95,65% participants. Poor practice was associated significantly with no availability of direct ophthalmoscope (p= 0.00038) that can not be accessed by 98 of participants (85%).Other GPs with ophthalmoscope access still did not conduct fundus examination because of no mydriasis to dilate pupil. Conclusion: Knowledge and attitude on fundus examination among GPs was good, but poor for practice. It was associated with direct ophthalmoscope and mydriasis availability. It need advocation approach to overcome.